2019
DOI: 10.1002/wea.3454
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort and heat stress indices for outdoor occupations over 15 years: a case study from Iran

Abstract: The present study aims to assess seasonal trends in thermal comfort and heat stress indices for outdoor occupations over a 15‐year period using the Iranian Meteorological Organization's database for Sari, Iran. Hourly and daily meteorological data including temperature, wind speed, cloudiness, relative humidity and vapor pressure measurements for Sari city from 2000 to 2014 are used. The wet‐bulb globe temperature (WBGT) and universal thermal climate index (UTCI) are calculated, along with thermal comfort indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Moreover, similar to the results from most of the previous studies in this field, the present study demonstrated that there is a significant correlation coefficient between the measured environmental data and the meteorological data, justifying the efficiency of using this data for environmental issues (Ghalhari, Dehghan et al 2019, Golbabaei, Heidari et al 2019, Heidari, Golbabaei et al 2019.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, similar to the results from most of the previous studies in this field, the present study demonstrated that there is a significant correlation coefficient between the measured environmental data and the meteorological data, justifying the efficiency of using this data for environmental issues (Ghalhari, Dehghan et al 2019, Golbabaei, Heidari et al 2019, Heidari, Golbabaei et al 2019.…”
Section: Discussionsupporting
confidence: 89%
“…Almost 82% of Iran's territory is located in arid and semi-arid zones. These regions, which are mostly located near the center and southern parts of the country, experience very hot summers (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Global warming and climate change have become one of the most controversial issues these days, affecting the health of people and threatening human life [1]. According to the definition of the United Nations Framework Convention, climate change is any variation in climatic conditions that differs with atmospheric compounds in the past and directly or indirectly affects the human activity [2].Global warming can profoundly impact people's physical activity patterns. It may influence people's work-related and leisure-time physical activity through rising temperatures, extreme weather conditions, and resulting changes in human activities (e.g., urbanization, agricultural and industrial production) [3].…”
Section: Introductionmentioning
confidence: 99%